(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Il contributo, non sottoposto a valutazione, riproduce il testo della relazione, ampliata e con note, letta in occasione dell’incontro di studio “Intesa tra la Repubblica italiana e le Comunità islamiche: a che punto siamo?”, organizzato dalla I Commissione Affari Costituzionali della Camera dei Deputati in collaborazione con LUMSA, UNINT e Centro Studi Kore (Roma, 14 aprile 2016, Camera dei Deputati, Sala del Mappamondo). SOMMARIO: 1. Premessa - 2. L’Islam in Italia: una confessione religiosa non riconosciuta. - 3. La preliminare questione dei diritti - 4. Islam e questione immigratoria - 5. Natura delle comunità islamiche e laicità dello Stato - 6. Alcuni problemi sui contenuti di un’eventuale intesa - 7. Il pericolo di fughe in avanti - 8. Ostacoli da superare. Il problema dei luoghi di culto - 9. Una piccola proposta: le associazioni con finalità (o oggetto) mista - 10. La questione della rappresentatività. La proposta di una consulta dell’Islam italiano - 11. Il dialogo e la collaborazione a livello locale - 12. Osservazioni conclusive. Muslim Organisations in Italy: perspectives on an Agreement with the State ABSTRACT: This paper examines the legal framework of Muslim communities in Italy in order to check the requirements needed to reach an agreement with the State, as envisaged by the Italian Constitution for denominations other than Catholicism, whose relations with the State “are regulated by law, based on agreements with their respective representatives” (Art. 8, co. 3, Const.). Nowadays the problem is a key issue in current political debates both in Italy and in most European countries. This type of agreement could not only promote the social and cultural integration of Muslim communities into society, but also help isolate Islamic terrorists and their supporters in immigrate communities and fight them better. Given that in Italy Muslim communities and their members, including foreign ones, already enjoy all the civil and social rights that are granted by the Constitution to citizens and social groups, the analysis maintains that reaching such an agreement would be for the moment premature, on the basis of a number of reasons. Among these are the following: the deep divisions existing both within and among these communities, due to different ethnic and religious origins and settlement periods in Italy; the difficulty on behalf of the State to identify a reliable negotiating partner (or more than one) who really represents such communities and does not depend from foreign States. Last but not least the very nature of such an agreement appears to be questionable. In fact, on one hand it would bring relevant advantages and public funding but on the other it would also need an unconditional acceptance of human rights and of the fundamental principles of the Italian law system - among which the equality between men and women and State secularism - which still has to be fully acknowledged within these communities.